WORKPLACE SPIRITUALITY: EMPLOYEE CONNECTION TO WORK ENVIRONMENT AND WORKING CONDITIONS. - Kola-Olusanya, A.; Oginni, B.O.; Olaniyan, T.S.; Kasumu, M.S. (Farabi Journal of Social Sciences, 2025)
The study focused on workplace spirituality as a connector of the employee to the work environment and working conditions in the face of economic recession or depression by using the manufacturing organizations as the unit of analysis. The study identified the place of workplace spirituality in employee connection to work environment and working conditions and the relationship between all the components of workplace spirituality and work environment and working conditions. A questionnaire was used as the research instrument and was randomly administered to the respondents in the selected manufacturing organizations where in 187 copies of the questionnaires were found useable. It was found that workplace spirituality has a significant place in employee connection to the work environment and working conditions and that alignment of values one of the dimensions of workplace spirituality has a significant and positive relationship with the work environment and working conditions. It was concluded that employee connection to the work environment and working conditions in the face of economic recession or depression can be derived through the alignment of values, interconnectedness, and meaningful work. However, it was recommended that there should be a minimum safety benchmark for all the parties in the industrial organizations to prevent hazardous work environments and working conditions. Keywords: workplace spirituality, working life, work environment, employee well-being, working conditions, employee connection